Inheritance eaudiobook A memoir of genealogy, paternity, and love. - Shapiro, Dani (Random House Audio, 2019)
An Instant  NEW YORK TIMES  BESTSELLER A  LOS ANGELES TIMES, BOSTON GLOBE, WALL STREET JOURNAL,  and NATIONAL INDIE BESTSELLER A BEST BOOK OF THE YEAR according to  Elle, Real Simple , and  Kirkus Reviews “Memoir gold: a profound and exquisitely rendered exploration of identity and the true meaning of family.” — People Magazine “Beautifully written and deeply moving—it brought me to tears more than once.”—Ruth Franklin,  The New York Times Book Review   From the acclaimed, best-selling memoirist, novelist—“a writer of rare talent” (Cheryl Strayed)— and  host of the hit podcast  Family Secrets, comes  a memoir about the staggering family secret uncovered by a genealogy test: an exploration of the urgent ethical questions surrounding fertility treatments and DNA testing, and a profound inquiry of paternity, identity, and love. What makes us who we are? What combination of memory, history, biology, experience, and that ineffable thing called the soul defines us?      In the spring of 2016, through a genealogy website to which she had whimsically submitted her DNA for analysis, Dani Shapiro received the stunning news that her father was not her biological father. She woke up one morning and her entire history—the life she had lived—crumbled beneath her. Inheritance  is a book about secrets—secrets within families, kept out of shame or self-protectiveness; secrets we keep from one another in the name of love. It is the story of a woman's urgent quest to unlock the story of her own identity, a story that has been scrupulously hidden from her for more than fifty years, years she had spent writing brilliantly, and compulsively, on themes of identity and family history. It is a book about the extraordinary moment we live in—a moment in which science and technology have outpaced not only medical ethics but also the capacities of the human heart to contend with the consequences of what we discover.